A Practical Framework and Model for Promoting Cost-Inclusive Evaluations - Nadini Persaud (The Evaluation Center at Western Michigan University, 2018)
Background: Cost studies are an important component of any serious professional evaluation. Regardless of whether an evaluation is conducted in the public or private sector, decision-makers want answers to two fundamental questions: (1) Is the program, project, or investment worthwhile? and (2) Can funds be used in a better way? The answers to both questions rely on the use of cost analysis techniques. However, according to the literature, most evaluations do not include any type of cost study (see Christie & Fleischer, 2010) and when studies are included, very few are of high quality and rigor (see Madsen, Eddleston, Hansen, & Konradsen, 2017). This may in part be as a result of the relatively limited emphasis placed on this important topic in the evaluation-specific literature, coupled with the reality that many evaluators lack expertise to conduct cost analysis studies. Purpose: Given the limited use of cost studies in professional evaluations to assess actual program merit/worth, this paper presents a practical framework/model to help evaluators understand fundamental issues that must be considered when thinking about some form of cost-inclusive evaluation. Setting: Not Applicable. Intervention: Not Applicable. Research Design:  External desk research was used to ascertain the extent to which cost analysis is discussed in the evaluation literature and the reasons highlighted for underuse. This review provided the foundation for developing the practical framework/model presented in this paper for promoting cost-inclusive evaluation. Data Collection and Analysis: Not Applicable. Findings: Cost analysis, which can considerably enrich professional evaluations, is currently quite underused in the evaluation profession. Notable progress has been made over the last 15 years with government agencies around the globe taking the lead to promote cost analysis. However,  most independent evaluators are still failing to measure, report, and analyze costs because many do not understand the fundamentals of cost studies. This paper promotes cost-inclusive evaluation by providing evaluators with a framework/model to help them understand important issues in cost analysis.                   Keywords: cost-analysis, costs, cost studies, benefits, evaluation, framework, measurement, model, valuation.